The Poetics of Love in al-Asma’i’s Poetry Sawt Shafiri Bulbuli (A Roman Jakobson Poetic Function Analysis): Puisi Cinta dalam Puisi al-Asma'i Sawt Shafiri Bulbuli (Analisis Fungsi Puisi Roman Jakobson) - Nur Robi Ari Saputra; Anwar Mas’adi (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Modern poetry surpasses artistic and academic limits, serving as a medium for reflection, social critique, and shared expression. Its enduring relevance derives from Roman Jakobson’s poetic function, emphasizing rhythm, rhyme, parallelism, and metaphor. This study explores that function in al-Asma?i’s classical Arabic poem ?awt ?af?ri al-Bulbul?, focusing on phonological and syntactic elements that shape its aesthetic impact. This study applies a qualitative method using a structuralist approach. The primary data come from al-Asma?i’s I?lamu an-N?si bim? Waqa?a lil-Baramakah ma?a Ban? al-?Abb?si (Dar al-Kutub al-?Ilmiyyah). The analysis includes close reading, identification of phonological elements (assonance and alliteration) and syntactic structures, followed by data reduction and interpretation within Jakobson’s framework of language functions. The analysis of al-Asma?i’s classical Arabic poem ?awt ?af?ri al-Bulbul? across phonological, syntactic, and semantic levels reveals the prominence of the poetic function. Phonologically, repeated consonants and vowels generate a musical tone akin to birdsong. Syntactically, sentence variations create balance and enhance aesthetic appeal. Semantically, metaphor and metonymy highlight expressive form rather than literal meaning. This study concludes that the aesthetic value of ?awt ?af?ri al-Bulbul? resides not only in its thematic content but also in its linguistic structure. Jakobson’s principle of equivalence between the axes of selection and combination serves as the core mechanism shaping the poem’s aesthetic effect. Hence, examining the poetic function enables a deeper understanding of poetry as a linguistic art form grounded in creativity and socio-cultural context.